ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN TUNNELING INCENTIVE TERHADAP KEPUTUSAN PERUSAHAAN UNTUK MELAKUKAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SEKTOR CONSUMER NON-CYCLICALS DI BURSA EFEK INDONESIA TAHUN 2015-2021 - Salwa, Amirah; Wahyudi, Ilham; Olimsar, Fredy (Jambi Accounting Review (JAR), 2024)
This study aims to empirically prove the effect of profitability, leverage, and tunneling incentive on the Company's decision to transfer pricing in manufacturing companies in the consumer non-cyclicals sector on the Indonesia Stock Exchange in 2015-2021. The independent variables in this study were profitability, leverage, and tunneling incentive. While the dependent variable is transfer pricing which is measured using the CETR proxies. The sample used in this study is a consumer non-cyclicals sector manufacturing company listed on the Indonesia Stock Exchange obtained as many as 16 companies. The analysis method in this study is simple linear regression. The results showed that variable profitability and tunneling incentive partially had a significant positive effect on transfer pricing. While leverage partially does not have a significant effect on transfer pricing.